2009
DOI: 10.1007/s11276-009-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Semantic-based resource discovery, composition and substitution in IEEE 802.11 mobile ad hoc networks

Abstract: We present a general framework for resource discovery, composition and substitution in mobile ad-hoc networks, exploiting knowledge representation techniques. Key points of the proposed approach are: (1) reuse of discovery information at network layer in order to build a fully unified semantic-based discovery and routing framework; (2) use of semantic annotations in order to perform the orchestration of elementary resources for building personalized services adopting a concept covering procedure, and to allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In the experiment, we have demonstrated that the QoSAWF schema is capable of describing the interaction scenarios required by the CineGrid use case. Compared to the network resource discovery in the Mobile Ad-hoc NETworks (MANETs) [44], our approach more focuses on the circuit network and on the large data movements, although both work share changing network routings behaviour as the common objective.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment, we have demonstrated that the QoSAWF schema is capable of describing the interaction scenarios required by the CineGrid use case. Compared to the network resource discovery in the Mobile Ad-hoc NETworks (MANETs) [44], our approach more focuses on the circuit network and on the large data movements, although both work share changing network routings behaviour as the common objective.…”
Section: Discussionmentioning
confidence: 99%
“…In some approaches [2], [4], resources are pre-selected by matching only the reference ontology identifier and ancillary extra-logical, data-oriented attributes w.r.t. the request.…”
Section: Challengesmentioning
confidence: 99%
“…Therefore, we deem that avoiding full decompression is important to improve efficiency of on-the-fly query processing. Finally, a suitable communication protocol (e.g., extending the ones in [2], [4]) is needed to support semantic requests and replies among MANET hosts, but that is outside the scope of the paper.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a network goal and a set of available services/resources both described using a subset of logic-endowed languages, it can be possible to carry out discovery and composition simple components covering as much as possible the needs of the system. Moreover, to increase the fault tolerance, the composition protocol integrates an automatic substitutability among resource components [9]. In this context one of main goal of the project is to prove that it is possible to apply in real systems the above described technologies, improving at the same time obtained performances.…”
Section: Introductionmentioning
confidence: 99%